Sex and Cognitive Ability‐Based Stratification of Social Attention in Autism - Jason W. Griffin; Frederick Shic; Adam Naples; Kelsey Dommer; Geraldine Dawson; Susan Faja; Shafali Jeste; Natalia Kleinhans; James Dziura; Catherine Sugar; Damla Senturk; Gerhard Hellemann; et al. (Autism Research, 2026)
ABSTRACT Reduced social attention (SA) is a hallmark feature of autism that is foundational to social communication and interaction. However, emerging evidence suggests that reduced SA may not be uniformly expressed across the autism spectrum. Sex and cognitive ability (IQ) have been identified as relevant stratification variables, potentially moderating SA in autistic children. We examined differential patterns of SA stratified by sex and cognitive ability in a large, longitudinal sample of autistic and neurotypical (NT) children (ages 6–11 years) from the Autism Biomarkers Consortium for Clinical Trials (ABC‐CT), examining SA across four measurement timepoints (Baseline, 6 weeks, 6 months, and 4 years). SA was measured using the oculomotor index of gaze to human faces (OMI) derived from standardized eye‐tracking (ET) assays, with children stratified by sex (male, female) and IQ (IQ ≥ 85, IQ < 85). Linear mixed‐effects models were used to evaluate the effects of sex, IQ, and timepoint on SA, with additional analyses assessing the stability and clinical associations of OMI. Autistic females did not exhibit lower OMI scores compared to autistic males; however, relative to sex‐matched NT children, autistic females showed approximately twice the reduction in OMI observed in autistic males. Likewise, the reduction in OMI associated with autism (i.e., ASD < NT) was larger in autistic children with below‐average IQ than in those with average or above‐average IQ. These differences were relatively stable across measurement timepoints, and OMI was more strongly associated with clinical features like face memory and adaptive behavior in autistic males and the average or above‐average IQ autism subgroup. While reduced SA is a general feature of autism, its expression is stratified by sex and cognitive ability. These findings highlight the importance of subgroup stratification to better understand heterogeneity in autism and improve the utility of SA as a therapeutic biomarker.